Surveying Human Vulnerabilities across the Life Course - Oris, Michel; Roberts, Caroline; Joye, Dominique; Ernst Stähli, Michèle (Life Course Research and Social Policies,, 2016)
This open access book details tools and procedures for data collections of hard-to-reach, hard-to-survey populations. Inside, readers will discover first-hand insights from experts who share their successes as well as their failures in their attempts to identify and measure human vulnerabilities across the life course. Coverage first provides an introduction on studying vulnerabilities based on the Total Error Survey framework. Next, the authors present concrete examples on how to survey such populations as the elderly, migrants, widows and widowers, couples facing breast cancer, employees and job seekers, displaced workers, and teenagers during their transition to adulthood. In addition, one essay discusses the rationale for the use of life history calendars in studying social and psychological vulnerability while another records the difficulty the authors faced when trying to set-up an online social network to collect relevant data. Overall, this book demonstrates the importance to have, from the very beginning, a dialogue between specialists of survey methods and the researchers working on social dynamics across the life span. It will serve as an indispensable resource for social scientists interested in gathering and analyzing data on vulnerable individuals and populations in order to construct longitudinal data bases and properly target social policies.